Stress Tests on Dye-sensitized Solar Cells with the Cs2SnI6 Defect Perovskite as Hole-transporting Material. (December 2016) - Kaltzoglou, Andreas; Perganti, Dorothea; Antoniadou, Maria; Kontos, Athanassios G.; Falaras, Polycarpos
Abstract: Inorganic tin perovskites appear as highly efficient materials for dye-sensitized solar cells. Despite their promising characteristics such as low cost and lack of toxicity, the stability of the corresponding devices still remains an issue to be addressed. In the current study, the chemical reactivity of the defect perovskite Cs2 SnI6 at various temperatures and under illumination as well as the ageing of Cs2 SnI6 -based solar cells are investigated. According to X-ray powder diffraction analysis, gradual decomposition of the perovskite in ambient air only occurs at temperatures above 80 °C. Dye-sensitized solar cells were fabricated using the Z907 metal-organic complex as photosensitizer and Cs2 SnI6 as hole transporter on mesoporous TiO2 substrate. The power conversion efficiency remains constant at 3.3% when the solar cell is stored at room temperature in the dark. Successive current-voltage measurements after exposure of the device to 40 °C for up to 200 hours revealed a marked effect on the photovoltaic performance. Electrochemical impedance spectroscopy was also employed to identify the correlation between the photoelectrochemical properties and the relevant behavior of the device components upon ageing.